2023
DOI: 10.1002/edn3.425
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of community science monitoring with environmental DNA for marine fish species: “Fish survey project using environmental DNA

Abstract: Environmental DNA is a powerful tool for community science‐based biodiversity surveys. However, the effectiveness of environmental DNA for environmental education and the time and physical costs perceived by volunteers for collecting environmental DNA remain unclear. Here, we evaluated a community science program for monitoring marine fish biodiversity using environmental DNA metabarcoding. This program aimed to investigate marine fish biodiversity in coastal areas along the Japanese archipelago. The participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Importantly, it has been shown that citizen scientists with minimal training are effective in eDNA sampling [ 72 ], thus opening participation to people who have previously been under-served, and participants can even be involved in the corresponding laboratory analyses [ 81 , 82 ]. Furthermore, such participation can enhance citizen scientists' understanding of biodiversity, ecosystems, and the principles of eDNA [ 73 , 83 ]. A further step could be the development of commercially available in-field diagnostic tests, similar to the COVID-19 lateral flow tests, which could be developed for rare or invasive species [ 74 , 84 ].…”
Section: Technology As An Enabler—opening Up New Research Avenuesmentioning
confidence: 99%
“…Importantly, it has been shown that citizen scientists with minimal training are effective in eDNA sampling [ 72 ], thus opening participation to people who have previously been under-served, and participants can even be involved in the corresponding laboratory analyses [ 81 , 82 ]. Furthermore, such participation can enhance citizen scientists' understanding of biodiversity, ecosystems, and the principles of eDNA [ 73 , 83 ]. A further step could be the development of commercially available in-field diagnostic tests, similar to the COVID-19 lateral flow tests, which could be developed for rare or invasive species [ 74 , 84 ].…”
Section: Technology As An Enabler—opening Up New Research Avenuesmentioning
confidence: 99%
“…Coupling citizen science with eDNA monitoring is a promising approach in both marine (e.g., Tøttrup et al, 2021;Agersnap et al, 2022;Suzuki-Ohno et al, 2023) and freshwater habitats (Biggs et al, 2015). Citizen science involvement in eDNA monitoring allows for broader geographical sampling and public engagement in biodiversity research (Agersnap et al, 2022), including educational benefits (Tøttrup et al, 2021;Knudsen et al, 2023).…”
Section: Citizen Sciencementioning
confidence: 99%
“…apply metabarcoding, similar to the studies performed byAgersnap et al (2022) andSuzuki-Ohno et al (2023).…”
mentioning
confidence: 98%